Treating ER-positive breast cancer: a review of the current FDA-approved SERMs and SERDs and their mechanisms of action - Nayoung Kim; Kiven Erique Lukong (Oncology Reviews)
Breast cancer is one of the most significant causes of mortality among women and the second most prevalent cancer worldwide. Estrogen receptor (ER)-positive breast cancers are the most common molecular subtype of breast cancer, comprising about 70% of breast carcinoma diagnoses worldwide. Endocrine therapy is the foremost strategy for the treatment of ER-positive breast cancer. In the United States, the Food and Drug Administration (FDA) has approved endocrine therapies for ER-positive breast cancers that include selective estrogen receptor modulators (SERMs), selective estrogen receptor downregulators/degraders (SERDs) and aromatase inhibitors (AIs). The approved SERMS, tamoxifen, toremifene and raloxifene, are the gold-standard treatments. The only FDA-approved SERD available for treating ER and hormone-positive breast cancers is fulvestrant, and various generations of AIs, including exemestane, letrozole, and anastrozole, have also received FDA approval. Herein, we review the major FDA-approved SERMs and SERDs for treating ER-positive breast cancer, focusing on their mechanisms of action. We also explore molecular events that contribute to the resistance of these drugs to endocrine therapies and combinational strategies with drugs such as cyclin-dependant kinases 4/6 (CDK4/6) inhibitors in clinical trials to combat endocrine drug resistance.